Respostas
respondido por:
3
x² + (x + 1)² = 25
x² + (x + 1) . (x + 1) = 25
x² + x² + x + x + 1 = 25
2x² + 2x + 1 - 25 = 0
2x² + 2x - 24 = 0
a = 2; b = 2; c = - 24
Δ = b² - 4ac
Δ = 2² - 4 * 2 * (- 24)
Δ = 4 + 192
Δ = 196
x = - b ± √Δ
-------------
2a
x = - 2 ± √196
----------------
2 * 2
x = - 2 ± 14
--------------
4
x' = (- 2 + 14) ÷ 4
x' = 12 ÷ 4
x' = 3
x'' = (- 2 - 14) ÷ 4
x'' = - 16 ÷ 4
x'' = - 4
Resposta: (3; - 4)
x² + (x + 1) . (x + 1) = 25
x² + x² + x + x + 1 = 25
2x² + 2x + 1 - 25 = 0
2x² + 2x - 24 = 0
a = 2; b = 2; c = - 24
Δ = b² - 4ac
Δ = 2² - 4 * 2 * (- 24)
Δ = 4 + 192
Δ = 196
x = - b ± √Δ
-------------
2a
x = - 2 ± √196
----------------
2 * 2
x = - 2 ± 14
--------------
4
x' = (- 2 + 14) ÷ 4
x' = 12 ÷ 4
x' = 3
x'' = (- 2 - 14) ÷ 4
x'' = - 16 ÷ 4
x'' = - 4
Resposta: (3; - 4)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás